Contrasting fates of subducting carbon related to different oceanic slabs in East Asia. (1st May 2022) - Liu, Sheng-Ao; Wu, Tianhao; Li, Shuguang; Wang, Zhaoxue; Liu, Jingao
Abstract: Subduction transfers surface carbon into the Earth's interior in a main form of carbonates that influences the global carbon cycles and surface climate through geologic time. Nevertheless, whether the fate of downgoing carbonates significantly varies in past subduction zones is rarely constrained by natural observations. Marine carbonates have remarkably higher zinc isotopic ratios (expressed as δ 66 ZnJMC-Lyon ) relative to the mantle (0.99 ± 0.24‰ vs. 0.18 ± 0.05‰), making zinc isotopes a sensitive tracer for subducting carbonates. Here we examine this issue through a comparative zinc isotope study on basalts across the North-South Gravity Lineament (NSGL) in East Asia that were genetically related to two different oceanic slabs. Together with existing data, we show that all basalts in the east of the NSGL have high δ 66 Zn (∼0.3–0.6‰; n = 134) that do not vary with distances to the trench and are spatially coupled with the horizontally stagnated slab in the transition zone (410– 660 km). This indicates that subducting carbonates survived shallow dissolution and were deeply buried during westward subduction of the Paleo-Pacific slab. By contrast, basalts in the west of the NSGL display a gradual decline of δ 66 Zn from 0.50 ± 0.04‰ to 0.28 ± 0.03‰ ( n = 35) with increasing distances to the trench. No known magmatic processes (e.g., partial melting, crystal-melt differentiation, melt-peridotite interaction, and degassing) can account for the spatial Zn isotopic variation. The role of slab-derived sulfate rich fluids is also excluded because of the mantle-like Cu isotopic compositions of these basalts. Instead, the gradual decrease of δ 66 Zn, together with the coupled decline of CaO/Al2 O3, are best explained as the diminished amounts of dissolved carbonates in their mantle sources. Thus, substantial carbonate dissolution must have occurred during southeastward subduction of the Paleo-Asian slab, which prevents deep burial of subducting carbon. The main differences between the two large slabs include: (i) the Paleo-Asian slab has an extended longevity (∼1.1 Ga) and slow spreading rate in comparison with the Paleo-Pacific slab, leading to the main incorporation of carbonate minerals into the altered oceanic crust, and (ii) the younger Paleo-Pacific slab contains abundant deep-sea Mg-rich carbonates that were not sufficiently dissolved at shallow depths. These differences demonstrate that subduction of different oceanic slabs can lead to contrasting fates of subducting carbon in ancient subduction zones, depending on the contents and species of carbonate sediments in the oceanic crust.